The end of populism : twenty proposals to defend liberal democracy - Herpen, Marcel H. van, 1945- (Manchester University Press, 2021)
This book proposes concrete solutions to confront the populist wave and the rise of ""illiberal democracy."" The author demonstrates that democracy is not a ""demand side"" phenomenon, but rather a ""supply side"" phenomenon and formulates twenty original and bold proposals to fight populism and defend liberal democracy. An original and essential book which will undoubtedly stimulate vigorous debate.